STUDI PENENTUAN TINGKAT KUALITAS AIR SUNGAI BERDASARKAN METODE INDEKS KUALITAS AIR – NATIONAL SANITATION FOUNDATION (NSF-IKA) SEBAGAI DASAR PENENTUAN RENCANA AKSI PENGELOLAAN SUNGAI (Studi Kasus Sungai Tuntang, Jawa Tengah) - Niken Anggraeni P (Jurnal Teknik Lingkungan, 2012)
Tuntang river has 111.319 km long river, is one of the rivers located in Java, which has an important role for residents with daily activities around the river. Watershed Tuntang past several environmental setting such as residential, agriculture and plantations, which could potentially degrade water quality in the river water bodies. River water quality determination method Tuntang-Water Quality Index's National Sanitation Foundation (NSF-IKA). Tuntang River water quality monitoring conducted at 9 segments and 12 sampling points. The results obtained from the calculation of the NSF-IKA status of segmen one is good, segment two to segment nine is the status of medium. Land use in the surrounding watershed can affect water quality Tuntang Tuntang River. Pollutant sources are dominant Tuntang River BOD, turbidity, and fecal coliform caused by domestic waste, plantations, agricultural waste into rivers and erosion. In such conditions the proposed river management to do is provision for residents around the septic tank, the optimal use of fertilizer, reforestation and community participation in maintaining the water quality of the river Tuntang.